Affections Neuroméningées Au Cours Du VIH Dans Le Service Des Maladies Infectieuses Du CHU De Brazzaville : Prévalence Et Facteurs Associés Au Décès - Ossibi Ibara Bienvenu Rolland, Obengui; Damba Banzouzi Bébene; Ossou-Nguiet Paul Macaire; Paka Herdan; Boumandouki Paul Jean Claude; Puruenhce Marie Francke (European Scientific Journal, ESJ, 2016)
Goal . Neuromeningeal determine the prevalence of disease in PLHIV and identify factors associated with death. Methodology. Retrospective study on descriptive and analytical referred cases hospitalized in the Infectious Diseases department during the period 1 January 2013 to 31 May 2015. Results. One hundred and fifty patients included (10.5% of admissions) with mean age of 41.1 ± 11.8 years (range 19 to 69) women (n = 86, 57.3%), sex ratio of 1,3. were without jobs (n = 68; 45.3%), single (n = 96; 64%), heterosexually infected by HIV-1 (100%). The average time of consultation was 19.2 ± 1.3 days. Fever (n = 99; 66.0%), disorders of consciousness (n = 66; 44.0%) were the main reasons for consultations. Meningeal stiffness (40%), focal signs (n =62; 41,4%) were the main signs consideration. CSF was clear (n = 94; 62.7%), hyperproteinorachique (59.8%), hypoglycorrachique (43.8%). Examining the ink was positive in 39 cases (34.8%) The Gerh was positive in 35 patients .the CT abnormalities were dominated abscess (n = 12; 15.4%).. Thirty four patients were on TDF + FTC + EFV regimen. The average hospital stay was 14.4 ± 9.5 days. Overall mortality was 83.2% mainly due to cerebral herniation (n = 28; 33.3%). Conclusion. The prevalence and lethality of diseases neuromeningeal of HIV are high. The diagnosis delay and TNM influence the prognosis of patients; Hence the importance of early detection of HIV infection for its management to prevent immunosuppression.